Editorial: Vol 30 (2014) of the Southern African Journal of Environmental Education (SAJEE) - Lausanne Olvitt (Environmental Association of Southern Africa, 2014)
This year marks the end of the United Nations Decade of Education for Sustainable Development which was first proposed at the World Summit on Sustainable Development in 2002 in Johannesburg. At the end of 2014 UNESCO hosted the World Conference on Education for Sustainable Development in Nagoya, Japan. To mark this occasion Professor Rob O'Donoghue produced a reflective Think Piece that traces the emergence of education for sustainable development (ESD) from its educational roots in the Modernist project, to thediversity of practices that currently frame ESD as a transgressive process of cultural change. O'Donoghue interrogates tensions around knowledge and participation in the ESD terrain and proposes that knowledge-led and ethics-led learning in relation to valued purposes might create educational possibilities for expansive, transgressive and reflexive learning processes towards a more sustainable future. This Think Piece opens the Journal; many of the strengths, tensions and generative opportunities in environment and sustainability education referred to by O'Donoghue are reflected in this edition of the journal.